Identification of Novel Melanin Synthesis Inhibitors From Crataegus pycnoloba Using an in Vivo Zebrafish Phenotypic Assay - Agalou, Adamantia; Thrapsianiotis, Michael; Angelis, Apostolis; Papakyriakou, Athanasios; Skaltsounis, Alexios-Leandros; Aligiannis, Nektarios; Beis, Dimitris (Frontiers in Pharmacology, 2018)
Zebrafish has emerged as a powerful model organism for high throughput drug screening. Several morphological criteria, transgenic lines and in situ expression screens have been developed to identify novel bioactive molecules and their mechanism of action. Here we used the inhibition of melanogenesis during early zebrafish embryo development to identify natural compounds that block melanogenesis. We identified an extract from the greek hawthorn Crataegus pycnoloba as a potent inhibitor of melanin synthesis and used activity based sub-fractionation to identify active subfractions and eventually three single compounds of the same family (dibenzofurans). These compounds show reversible inhibition of melanin synthesis and do not act via inhibition of Tyrosinase. We also showed that they do not interfere with neural crest differentiation or migration. We identified via in silico modeling that the compounds can bind to the Aryl Hydrocarbon Receptor (AHR) and verified activation of the AHR signaling pathway showing the induction of the expression of target genes.